2013
DOI: 10.1155/2013/784176
|View full text |Cite
|
Sign up to set email alerts
|

A Novel del(20q) in Aggressive Nodal Marginal Zone Lymphoma

Abstract: This is a case report of a previously undescribed 20q chromosomal deletion (del(20q)) in marginal zone lymphoma (MZL). A 54-year-old Caucasian male presented with an enlarging neck mass and multiple violaceous skin nodules over his chest. Biopsy of the neck mass and cervical lymph nodes revealed MZL. Cytogenetic evaluation of both lymph node and bone marrow tissue revealed del(20q). This was an unexpected finding, as del(20q) is associated with myelodysplastic syndromes and myeloproliferative neoplasms and rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
0
10
1
Order By: Relevance
“…Deletion of chromosome 20q is a common cytogenetic abnormality in various myeloid neoplasms, most notably myelodysplastic syndrome [1, 13, 14] but its association with lymphoid malignancies is rare and limited to a few reports. This includes a case of lymphoplasmacytic lymphoma/Waldenström macroglobulinemia [15] and two cases of marginal zone lymphoma [12, 16]. Another study of 64 patients with chronic lymphocytic leukemia (CLL) revealed that del(20q) appears to be a therapy-related abnormality in CLL involving both myeloid and lymphoid cells and may represent disease progression [17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of chromosome 20q is a common cytogenetic abnormality in various myeloid neoplasms, most notably myelodysplastic syndrome [1, 13, 14] but its association with lymphoid malignancies is rare and limited to a few reports. This includes a case of lymphoplasmacytic lymphoma/Waldenström macroglobulinemia [15] and two cases of marginal zone lymphoma [12, 16]. Another study of 64 patients with chronic lymphocytic leukemia (CLL) revealed that del(20q) appears to be a therapy-related abnormality in CLL involving both myeloid and lymphoid cells and may represent disease progression [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous report described del(20q) in MZL with aggressive features [12]. Since this patient’s DLBCL was thought be derived from a MZL, additional FISH analysis for a 20q12 deletion was performed on both skin and lymph node material to determine whether this abnormality may be present.…”
Section: Case Presentationmentioning
confidence: 99%
“…Deletions in the long arm of chromosome 20 ‐ del(20q), generally centered on 20q12 ‐ are commonly associated with myeloid neoplasms, most notably myelodysplastic syndrome (MDS), myeloproliferative disorders and acute myeloid leukemia . Although rarely associated with lymphoma, del(20q12) has been reported in a case of aggressive NMZL . We recently described a case of DLBCL harboring del(20q12) in a patient with a history of MZL involving lymph nodes and skin .…”
Section: Introductionmentioning
confidence: 99%
“…The incidental finding of 20q‐ in the bone marrow has been observed in the absence of MNs . Such cases may or may not present with cytopenias and the bone marrow may have minimal or no atypical features.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated finding of 20q‐ has been rarely reported in the lymphoproliferative disorders . A recent study described the isolated finding of 20q‐ in CLL patients post treatment.…”
Section: Discussionmentioning
confidence: 99%